Revitalizing National Identity and Social Harmony: A Cross-sectional Study of Nusantara Cultural Integration in Pupil Management and Stakeholder Support - Imron, Ali; Rasdiana, Rasdiana; Wiyono, Bambang Budi; Prestiadi, Dedi; Wahed, Andi; Maulina, Sasi; Redjeki, Dwi Sogi Sri; Margariena, Ika Nova; Puspitasari, Eka (Journal of Posthumanism, 2025)
Preserving Indonesian cultural values amidst globalization plays a crucial role, especially in facing challenges such as symbolic degradation, declining trust in national culture, and decreasing nationalism among the younger generation. This study aims to explore the impact of integrating Archipelagic cultural values into pupil management, pupil management activities, and stakeholder support on the revitalization of national identity and social harmony in formal schools in Indonesia. This study uses a quantitative survey approach with multiple linear regression, employing IBM SPSS, AMOS for Confirmatory Factor Analysis (CFA), and Smart PLS 3 for hypothesis analysis. Data were collected from 268 respondents selected randomly from the population of school principals, vice principals, teachers, students, student organization advisors, and school staff across various provinces in Indonesia. The study results indicate that integrating Archipelagic cultural values in pupil management and culture-based pupil management activities significantly impacts the revitalization of national identity and social harmony. However, stakeholder support did not significantly affect it. The study's limitations include potential constraints in sample size, geographic focus, and the complexity of capturing interactions between global and local cultural forces. Therefore, future research could explore dominant factors in revitalizing national identity and social harmony, the impact of social media on students' views of Archipelagic values, and use comparative studies to enhance insights on integrating local values in education. Furthermore, guides educators and school principals in designing curricula integrating Archipelagic cultural values to strengthen students' national identity. It highlights the importance of training principals and mentors to address the challenges of globalization while maintaining national cultural values.